The deubiquitinase USP5 prevents accumulation of protein aggregates in cardiomyocytes - Eibach, Yvonne; Kreher, Silke; Poetsch, Mareike S.; Kho, Ay Lin; Gaertner, Ulrich; Clemen, Christoph S.; Schröder, Rolf; Guo, Kai; Milting, Hendrik; Meder, Benjamin; Potente, Michael; Richter, Manfred; et al. (Science advances, 2025)
Protein homeostasis is crucial for maintaining cardiomyocyte (CM) function. Disruption of proteostasis results in accumulation of protein aggregates causing cardiac pathologies such as hypertrophy, dilated cardiomyopathy (DCM), and heart failure. Here, we identify ubiquitin-specific peptidase 5 (USP5) as a critical determinant of protein quality control (PQC) in CM. CM-specific loss of mUsp5 leads to the accumulation of polyubiquitin chains and protein aggregates, cardiac remodeling, and eventually DCM. USP5 interacts with key components of the proteostasis machinery, including PSMD14, and the absence of USP5 increases activity of the ubiquitin-proteasome system and autophagic flux in CMs. Cardiac-specific hUSP5 overexpression reduces pathological remodeling in pressure-overloaded mouse hearts and attenuates protein aggregate formation in titinopathy and desminopathy models. Since CMs from humans with end-stage DCM show lower USP5 levels and display accumulation of ubiquitinated protein aggregates, we hypothesize that therapeutically increased USP5 activity may reduce protein aggregates during DCM. Our findings demonstrate that USP5 is essential for ubiquitin turnover and proteostasis in mature CMs.
Gesehen am 24.07.2025